A thematic analysis of dimensions of spiritual care - Mohammad Abbasi; Narges Eskandari; Akram Heidari; Morteza Heidari; Sadegh Yoosefee; Seyed-Hasan Adeli; Abdolhassan Kazemi (Wolters Kluwer Medknow Publications, 2022)
Background: An overview of spiritual care studies can help reveal the dimensions of spiritual care and summarize the findings of available studies. Thus, we designed the present study based on existing studies to explain the dimensions of spiritual care. Materials and Methods: In this thematic analysis, we gathered the related articles published in Persian and English in the last 8 years (2013-2021) with the help of the keywords of Care, Support, Spirituality, Religion, Treatment, Hospice, and Palliative, and searching in electronic databases, including PubMed, Scopus, Web Of Sciences, Magiran, Islamic Science Citation (ISC), and Scientific Information Database (SID). We accurately studied 79 articles that met the inclusion criteria, and then the spiritual care components were extracted and coded, and finally, the codes were categorized as themes and sub-theme. Results: Thematic analysis of available studies revealed that the dimensions (theme) of spiritual care include: spiritual and religious assessment, developing a structure for providing spiritual care, establishing effective and supportive communication with the patient, training the patient, answering his questions, encouraging, maintaining, and improving social communications, encouraging the patient to live happily, helping the patient to achieve peace and calmness, supporting for spiritual rituals and activities, supporting and training the patient's family, and supporting the dying patient. Conclusions: Spiritual care includes various and numerous dimensions. Considering the widespread dimensions of spiritual care, it seems necessary to design and plan appropriate studies to reveal other spiritual care dimensions from the perspective of patients and care providers in different cultures.